1995
DOI: 10.1001/jama.1995.03530080048040
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Criteria Used for Detecting Underuse of Coronary Revascularization

Abstract: Among patients meeting criteria for the necessity of revascularization, those receiving a revascularization procedure within 1 year had lower mortality than those treated medically. These results support the validity of the RAND/UCLA criteria for detecting underuse of these procedures, but more research is needed to confirm the findings and to determine the validity of guidelines for other procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(72 citation statements)
references
References 10 publications
1
71
0
Order By: Relevance
“…Studies using this method have shown that overuse [2][3][4][5][6][7][8][9][10][11] of invasive techniques in the management of coronary disease is uncommon, and attention has turned to the issue of underuse. [12][13][14][15][16] Well-designed expert panels can closely reflect the views of practicing physicians, 17 and methods for detecting the underuse of revascularization are highly reproducible. 18 Despite reports on the ratings of a large number of expert panels 2-11 on coronary revascularization, a central aspect of the validity of the appropriateness-rating method remains untested.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies using this method have shown that overuse [2][3][4][5][6][7][8][9][10][11] of invasive techniques in the management of coronary disease is uncommon, and attention has turned to the issue of underuse. [12][13][14][15][16] Well-designed expert panels can closely reflect the views of practicing physicians, 17 and methods for detecting the underuse of revascularization are highly reproducible. 18 Despite reports on the ratings of a large number of expert panels 2-11 on coronary revascularization, a central aspect of the validity of the appropriateness-rating method remains untested.…”
Section: Resultsmentioning
confidence: 99%
“…It is common for patients not to receive appropriate invasive treatment for coronary disease; 22 to 41 percent of patients for whom expert panels deem a procedure not only appropriate but also necessary do not undergo the procedure. [12][13][14][15][16] The only previous study of clinical outcomes 12 found retrospectively that, among patients for whom revascularization was deemed necessary, the rate of survival was higher and there was less chest pain among those who underwent revascularization than among those who were treated medically. However, the study was limited by insufficient statistical power to separate outcomes in patients undergoing percutaneous transluminal coronary angioplasty (PTCA) from those in patients undergoing coronary-artery bypass grafting (CABG).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…58 Other data are likewise supportive. 59 Similar tests of external validity of other consensus methods are less often reported.…”
Section: Consensus Methodsmentioning
confidence: 99%
“…Those receiving a revascularization procedure deemed necessary (concordant therapy) had a lower mortality and less chest pain at 2 years post procedure than those in whom revascularization was deemed necessary but who were treated with medical therapy (discordant therapy). 21 We therefore investigated clinical outcome in this selected population of catheterization laboratory patients to determine whether treatment that was concordant with the ratings of RAND, ACC/AHA, and RAS correlated with improved outcome and further to identify which clinical outcomes were best predicted by each system.…”
Section: Introductionmentioning
confidence: 99%